Al-Qur’an dan Problem Ekologi di Indonesia: Ekstensi Pemaknaan Kiamat Sugra dalam Tafsir Ilmi Kementerian Agama Indonesia - M. Agus Muhtadi Bilhaq; Inayah Rohmaniyah; Salim Rahmatullah (Nalar: Jurnal Peradaban dan Pemikiran Islam, 2023)
The minor resurrection (qiyamah al-sugra) was generally interpreted as the death of an individual human being, meaning that when a person dies, his or her resurrection has arisen. However, in the tafsir entitled Kiamat dalam Perspektif Al-Quran dan sains, the minor resurrection was scientifically interpreted and associated with various disasters, including ecological disasters due to human actions that damage the environment. Therefore, this study aims to understand the scientific meaning of the qiyamah al-sugra and assess its relevance to ecological problems in Indonesia. The method used in this research was qualitative in the form of library research. The data analysis methods used in this research include content analysis, hermeneutics, and inductive methods. This research resulted in several findings. First, the scientific interpretation of the qiyamah al-sugra implies an extension of meaning in which the minor resurrection was no longer limited to being defined as death and the beyond. Second, as an institutional interpretation, the scientific interpretation of the qiyamah al-sugra has a specific purpose in constructing ecological awareness in the audience of the tafsir, especially since ecological issues are one of the major concerns of the Indonesian government.